LAS CONTRIBUCIONES Y LOS DILEMAS DE LOS ESTUDIOS CUANTITATIVOS EN LAS CIENCIAS SOCIALES DE LA RELIGIÓN EN AMÉRICA LATINA = Contributions and dilemmas of quantitative studies in the Social Science of Religion in Latin America - Esquivel, Juan (Ciencias sociales y religión, 2020)
The path of the Social Sciences of religion in Latin America has been marked by qualitative studies. The stock of knowledge provided by the sociology and anthropology of religion from a qualitative perspective of research has generated the bases for the consolidation of this disciplinary orientation in the region. However, in recent decades, inquiries have multiplied from a quantitative approach, in order to measure the magnitude of the process of transformation of religious identities. The article aims to analyze comparatively the available statistical data on the religious phenomenon in Latin America, identifying its contributions and dilemmas. It focuses on religious affiliation, as the only data available and comparable at the regional level. Based on secondary sources, the surveys of the Pew Research Center and Latinobarómetro will be analyzed in the first place, and secondly, the data from de the Census and from Universities and National Research Centers. Despite the disparity in the corpus of statistical information between one country and another, the existing surveys coincide in highlighting a declining trend of Catholicism, with varying intensities according to each country, an increase in evangelical adhesions, as well as those without religious affiliation.